Chiral chromatography - Beesley, T. E. (New Delhi Wiley India, 1998)
The separation of chiral compounds is essential in drug synthesis, as normally only one of the mirror images (enantiomers) is active. Regulatory legislation is very tight in this area as the different 'handiness' of a compound can have a great effect on its function. There were a number of books on this subject published in the late eighties but most of these are now out of date if not out of print. This subject is still extremely important in the pharmaceutical industry and there is a demand for newer more up to date books which appears not to have been met by the number of books which have published in recent years. This book will add to these and will complement other titles in the Separation Science Series.
Keywords: PHARMACEUTICAL ANALYSIS